Effects of different additives on properties of magnesium aluminate Spinel–Periclase castable. Issue 3 (1st February 2023) - Wang, Shaoyang; Zhang, Ling; Huang, Min; Zheng, Peiyu; Hou, Qingdong; Qi, Xin; Li, Renjun; Chen, Lu; Luo, Xudong
Abstract: Bauxite- and alumina-based spinels were employed as refractory aggregates, and sintered magnesia fine powder, calcium aluminate cement, microsilica, and activated α-Al2 O3 were utilized as matrices. The effects of alumina powder, analytically pure zinc oxide, and analytically pure zirconia on the properties of magnesium aluminate spinel–periclase castables were studied. The results demonstrated that the addition of the three additives promoted the sintering of magnesium aluminate spinel–periclase castables. Simultaneously, the three additives significantly improved the high-temperature properties of the samples. The thermal shock resistance of the alumina powder sample increased by 200%, that of the pristine zinc oxide sample by 75%, and that of the zirconia sample by 125%. The additives effectively improved the thermal shock resistance of the magnesium aluminate spinel–periclase castable. In addition, the slag resistance depths of the samples with alumina powder and zirconia were 41% lower than that of the sample without additives, which significantly improved the slag resistance of the magnesium aluminate spinel–periclase castable.